Floppy Infant Syndrome: the Importance for the Differential Diagnosis of Hereditary Metabolic Diseases, and Degenerative Diseases of the Nervous System - T. M. Prygunova; T. M. Radaeva; E. Yu. Stepanova; E. E. Beresneva; I. A. Azovceva (Вопросы современной педиатрии, 2015)
The problem of clinical polymorphism rises sharply in the diagnosis of the conditions which are manifested by a floppy infant syndrome.It hasn’t nosological independence, its main clinical markers are nonspecific, and the course and outcome are variable. Diffuse muscular hypotonia can be a symptom of the majority of somatic and neurological diseases of infants, for example, genetic metabolic diseases, and degenerative diseases of the nervous system. Topically it is possible to classify it by levels of lesions to hypotonia of the central and peripheral origin, as well as to identify a number of criteria for their differences. This article describes the clinical cases of children with a floppy infant syndrome illustrating hypotonia of the central and peripheral lesion levels. It is described the opportunities and difficulties of the differential diagnosis, given the family history, prenatal and perinatal factors, the time the clinical picture manifestation. Different treatment strategy and prognosis of the opportunities in conducting habilitation determine the importance of the establishment of the topical level of the lesion. Due to the clinical significance of the floppy infant syndrome we should attract the attention of pediatricians, neurologists and parents to the question of determination of this syndrome in a child in order to promptly begin searching the causes of the condition and the complex therapy.